2005
DOI: 10.1074/jbc.c400433200
|View full text |Cite
|
Sign up to set email alerts
|

Maurocalcine and Domain A of the II-III Loop of the Dihydropyridine Receptor Cav 1.1 Subunit Share Common Binding Sites on the Skeletal Ryanodine Receptor

Abstract: Maurocalcine is a scorpion venom toxin of 33 residues that bears a striking resemblance to the domain A of the dihydropyridine voltage-dependent calcium channel type 1.1 (Ca v 1.1) subunit. This domain belongs to the II-III loop of Ca v 1.1, which is implicated in excitation-contraction coupling. Besides the structural homology, maurocalcine also modulates RyR1 channel activity in a manner akin to a synthetic peptide of domain A. Because of these similarities, we hypothesized that maurocalcine and domain A may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 26 publications
2
43
0
1
Order By: Relevance
“…The interaction of MCa with RyR1 has been witnessed by increased [ 3 H]ryanodine binding onto purified RyR1 (3,5). The binding site for MCa on RyR1 has also been mapped and shown to correspond to domain(s) that have a predicted localization within the cytoplasm (6). Second, similarly to imperatoxin A (7) for which this was first noted, MCa has an interesting sequence homology with the II-III loop of the L-type calcium channel Ca v 1.1 subunit over a domain that is slightly larger than the second ␤-strand of MCa (see Fig.…”
Section: Maurocalcine (Mca)mentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction of MCa with RyR1 has been witnessed by increased [ 3 H]ryanodine binding onto purified RyR1 (3,5). The binding site for MCa on RyR1 has also been mapped and shown to correspond to domain(s) that have a predicted localization within the cytoplasm (6). Second, similarly to imperatoxin A (7) for which this was first noted, MCa has an interesting sequence homology with the II-III loop of the L-type calcium channel Ca v 1.1 subunit over a domain that is slightly larger than the second ␤-strand of MCa (see Fig.…”
Section: Maurocalcine (Mca)mentioning
confidence: 99%
“…1A) (5). This loop is predominantly involved in excitation-contraction coupling through direct molecular interactions with RyR1 (6,8). This homology has been a source of inspiration to an understanding of how toxins may interfere with the process of excitation-contraction coupling (4,8,9).…”
Section: Maurocalcine (Mca)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ces observations avaient laissé entrevoir la possibilité que la maurocalcine devait traverser la bicouche lipidique des cellules afin d'exercer sa fonction d'activateur de canal calcique. Cette hypothèse était largement renforcée par le fait que le site d'interaction de la maurocalcine sur RyR1 est localisé dans une zone du cytoplasme [7]. La démonstration que la maurocalcine était effectivement un CPP est venue des observations suivantes : (1) l'application extracellulaire du peptide à des myotubes induit une libération calcique quasi instantanée [8] ; et (2) la greffe d'une protéine streptavidine fluorescente sur la maurocalcine biotinylée permet sa translocation intracellulaire [5].…”
Section: Peptides De Pénétration Cellulaire Et Mécanisme D'entrée Celunclassified
“…First, it was demonstrated that an extracellular application of L-MCa triggers an almost immediate Ca 2ϩ release from internal stores in myotubes, suggesting rapid access of L-MCa to its binding site (11). Second, it was discovered that the binding site of this toxin is located on the cytoplasmic side of RyR (12). Kinetic and RyR topological considerations therefore suggest that cell entry of L-MCa more likely relies on membrane translocation to achieve rapid cytoplasmic accumulation than on endocytosis.…”
mentioning
confidence: 99%